PERAN KEPALA SEKOLAH DALAM MENINGKATKAN KETERAMPILAN MENGAJAR GURU DI SDN 20 RUPAT - Rosmita (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This research was school action research conducted by the principal using descriptive methods. This research explained and described the research resultsbased on the facts found. This research was conducted at SDN 20 Rupat. The research subjectswere the teachers who taught at SDN 20 Rupat. The results of the research found an increase in teachers’ skills in teaching and an increase in teachers’ activity in learning after several actions taken by the principal against the teacher. The following is the data from the analysis of teachers’ teaching skills. The average percentage of teachers’ teaching skills was 79.4. The percentage on the indicator of opening and closing lessons was 75.5%. Then, the percentageon the questioning skill indicator was 82% and on the skill indicator of providing reinforcement to the students was 80.5%. Next, the percentage on the indicator of skills in conducting learning variations was 86.8% and the percentage on the skills of explaining lessons was 78.6%. Then, the percentage obtained on the indicator of skills in guiding small group discussions was 81.5%, and the percentage on the skills of managing class was 78%. Finally, the percentage on individual teaching skills obtained a percentage of 72.6%. It was concluded that the teaching skills of teachers at SDN 20 Rupat was categorized as good, so that the improvement of teachers’ teaching skills also improve students’ learning outcomes and increased the learning success.